2003
DOI: 10.1159/000072431
|View full text |Cite
|
Sign up to set email alerts
|

Low HBeAg Serum Levels Correlate with the Presence of the Double A1762T/G1764A Core Promoter Mutation and a Positive Response to Interferon in Patients with Chronic Hepatitis B Virus Infection

Abstract: Objective: To investigate the correlation of serum hepatitis B e antigen (HBeAg) levels with the presence of core promoter (CP) mutations, hepatitis B virus (HBV) viremia and the response to interferon (IFN) in patients with chronic hepatitis B. Methods: Fourteen HBeAg-positive patients received α-2a IFN. Diluted serum samples of responders were tested for HBeAg positivity at dilutions of 1:40, 1:160 and 1:640 at the following time points: T0 (before starting IFN), T1 [at peak alanine aminotransferase (ALT) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…In our study all patients but one showed wild type strain and before treatment had high viraemia and normal ALT values. Low serum HBeAg levels in combination with the double CP mutation A1762T/G1764A has also been associated to a positive response to IFN treatment [31,32]. This concurs with Boni et al [23], who has shown how an HBeAg decrease after lamivudine administration is concomitant with a drop in viraemia and a restoration of the T-cell response.…”
Section: Discussionsupporting
confidence: 54%
“…In our study all patients but one showed wild type strain and before treatment had high viraemia and normal ALT values. Low serum HBeAg levels in combination with the double CP mutation A1762T/G1764A has also been associated to a positive response to IFN treatment [31,32]. This concurs with Boni et al [23], who has shown how an HBeAg decrease after lamivudine administration is concomitant with a drop in viraemia and a restoration of the T-cell response.…”
Section: Discussionsupporting
confidence: 54%
“…The precore/core and promoter regions of HBV have been investigated continuously with emphasis on molecular parameters that would predict the outcome of interferon response on mainly genotypes A and D [Kanai et al, 1996;Erhardt et al, 2000;Marrone et al, 2003]. It has been considered that nucleotide changes within the basal (basic) core promoter (nucleotide regions 1742-1849) might be one of the determinants for maintaining or lowering of precore/core function and the level of HBV replication, because the basal core promoter controls the transcription of precore/core mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…A83 mutation in the HBV precore region, 1762-1764 double mutation and deletions in the core promoter region could enhance viral replication [Chen and Oon, 2000]. This could result in an inability to synthesize hepatitis B e antigen (HBeAg) [Marrone et al, 2003;Tacke et al, 2004] and increase the risk of hepatocellular carcinoma in hepatitis B carriers [Kao et al, 2003]. The mutations in 'a' determinant epitope of HBsAg may result in a vaccine escape mutation [Shizuma et al, 2003].…”
Section: Introductionmentioning
confidence: 99%